Helminth zoonoses of wild carnivore mammals in the Primorsky Krai of the Russian Far East - I. V. Seryodkin; O. P. Kurnosova; A. V. Khrustalev; N. V. Esaulova; A. I. Varlamova; I. M. Odoevskaya; И. В. Середкин; О. П. Курносова; А. В. Хрусталев; Н. В. Есаулова; А. И. Варламова; И. М. Одоевская (ВНИИП – филиал ФГБНУ ФНЦ ВИЭВ РАН, 2023)
The purpose of the research is to examine the helminthological status of wild carnivore mammals inhabiting the territory of the Primorsky Krai and to give an epidemiological assessment of their role in maintaining the natural foci of zoonotic infections.Materials and methods. Feces of carnivores were collected in natural habitats of wild animals. Species of animals were identified by the characteristic features of feces and animal tracks. The shape, size, texture and composition of feces were analyzed. The samples were placed in containers with 5% formalin. A part of the material was stored in native form at -12 ºС. Muscle tissue samples were obtained from animal carcasses. Feces were examined by flotation techniques with a solution of zinc sulfate, the formalin-ethyl acetate sedimentation technique and using an ammonium nitrate solution. After the study, the samples were disinfected by autoclaving at a pressure of 1.5 atm for 2 hours. Muscle tissue samples were examined by digesting in artificial gastric juice using the Gastros device. The species of Trichinella sp. larvae isolated from the positive samples were identified using the nucleotide sequences. In total, 444 feces samples from 13 species of wild carnivore mammals and 449 muscle tissue samples from 13 species were examined.Results and discussion. Wild carnivore mammals inhabiting the territory of the Russian Far East are often infected with various species of helminths localized in the intestine and tissues, which are causative agents of dangerous parasitic zoonoses. A total of 9 species of helminthes in the Siberian tiger (Panthera tigris altaica), 3 species in the Amur leopard (P. pardus orientalis), 2 species in the Eurasian lynx (Lynx lynx), 4 species in the leopard cat (Prionailurus bengalensis), 5 species in the sable (Martes zibellina), 2 species in the yellow-throated marten (M. flavigula), 5 species in the Siberian weasel (Mustela sibirica), 1 species in the American mink (Neovison vison), 2 species in the Asian badger (Meles leucurus), 8 ...